“Are you OK doctor?” An expanded health belief model exploration of doctors’ experiences and perspectives of on-shift health behaviour - Kirsty L. Hodgson; Daniel J. Lamport; Allán Laville (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Understanding doctors’ health beliefs is essential for developing effective and competent healthcare practices that benefit doctors and their patients. This study aimed to qualitatively explore doctors’ perceptions of on-shift health-protective behaviours and their perceived effects on competence. Methods The research applied theoretically driven Expanded Health Belief Model (EHBM) enquiry methods to explore beliefs and experiences through an occupational context survey, 14 individual depth interviews, and two focus groups. Semantic and deductive themes associated with EHBM domains were examined, and an inductive thematic analysis of the interviews was conducted. Results Doctors’ beliefs were strongly imbued by their perceived identity within the systemic context; they expressed impaired self-efficacy in reacting to their health needs on shift, and several disclosed harm to themselves and patients. Dominant themes included the psychosocial effects of the systemic culture and the influence of the situational occupational context in impacting health-protective behavioural action. The context and implications of experiences during the COVID-19 pandemic are discussed. Conclusions This study presents key belief-oriented factors influencing doctors’ health-protective behaviour at work and its implications for competent practice. Further doctor-led guidance on focus points for evidence-based theoretically driven health improvement solutions is provided regarding operational practice, formulating policies, developing interventions and further research.